A educação especial expressa no currículo para a rede pública municipal de ensino de Cascavel (PR): algumas reflexões - Rosa, Elcy Aparecida Silva (2023)
This dissertation presents a study on Special Education in the Curriculum for the Municipal Public Education Network of Cascavel (PR) - Elementary Education - early years, being first prepared in 2008 and re-elaborated in 2020, with the incorporation of the Common National Curricular Base. The objective of the research is to understand how Special Education is presented and can be implemented in the aforementioned Curricula, as it is part of the educational praxis, from the perspective of Inclusive Education. To achieve this, the research historically analyzes the conceptions of disability and the learning processes, human development and education, fundamental aspects of public policy on inclusive education and reflections carried out based on the analysis of special education present in the 2008 Curriculum and of its review in 2020, and how educational interventions are proposed for areas of disability. The theoretical methodological basis of the research is based on historical-dialectic materialism; the foundations of learning and development processes in Historical-Cultural Theory, and education in Historical-Critical Pedagogy, understanding that education is part of society and is determined by it, being in constant movement, making it necessary to overcome common sense. The research methodology consists of a literature review with a qualitative approach and descriptive bias, based on theoretical and documentary references. The understanding of public students in Special Education, in their possibilities for learning school content and human development, expands the role of teachers in their pedagogical practice in the quest to implement inclusive education.